2016
DOI: 10.1007/s10900-016-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Literacy in Reducing Negative Perceptions of Breast Health and Treatment Among Uninsured Primary Care Patients

Abstract: Breast cancer is the second leading cause of cancer death among women in the United States. There are disparities in breast cancer mortality by race/ethnicity and socio-economic factors. Health literacy may have an impact on breast health disparities. In addition, learning about people's perceptions of breast health and treatment is important to understand why some do not seek a mammogram or treatment for breast cancer. The purpose of this study is to examine the association between health literacy and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Women aware of their BD could more easily assess information within the health promotion domain based on the HLS-EU-Q47. In the current surveyed group of women, this subgroup had a higher level of education, which is consistent with literature data [ 22 , 34 , 35 ]. However, further research should clarify this result in more detail, and elucidate whether a higher level of health literacy could be a predictor of better BD awareness.…”
Section: Discussionsupporting
confidence: 92%
“…Women aware of their BD could more easily assess information within the health promotion domain based on the HLS-EU-Q47. In the current surveyed group of women, this subgroup had a higher level of education, which is consistent with literature data [ 22 , 34 , 35 ]. However, further research should clarify this result in more detail, and elucidate whether a higher level of health literacy could be a predictor of better BD awareness.…”
Section: Discussionsupporting
confidence: 92%
“…Those with low health literacy were more likely to report negative perceptions about breast cancer. For example, patients with low health literacy were more likely to endorse statements such as "If you have breast cancer, better not to know " and "the treatment for breast cancer is a long and painful process" and "embarrassing" 29 . Another study of 722 Mexican American women from Texas explored screening practices among women with inadequate or marginal health literacy.…”
Section: Disease-specific Knowledge and Screening Practicesmentioning
confidence: 99%
“…11 Another study on female free clinic patients suggests that female free clinic patients who have higher levels of health literacy are more likely to have lower levels of negative perceptions of breast cancer and treatment. 12 Further research is necessary to determine self-reported diagnoses of the 2 types of diabetes, including the relationship between health literacy and diabetesrelated health behaviors. The results on lifestyle change based on the regression analysis indicate that patients with type 2 diabetes only (based on perception) and/or patients of the diabetes clinic are not controlling their diabetes properly even if they receive comprehensive education on diabetes management.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another study on female free clinic patients suggests that female free clinic patients who have higher levels of health literacy are more likely to have lower levels of negative perceptions of breast cancer and treatment. 12 Further research is necessary to determine self-reported diagnoses of the 2 types of diabetes, including the relationship between health literacy and diabetes-related health behaviors.…”
Section: Discussionmentioning
confidence: 99%